2013
DOI: 10.1007/s12560-013-9132-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Enteroviruses in Influent and Effluent Flow Samples from Wastewater Treatment Plants in Italy

Abstract: This study evaluated the presence and seasonal distribution of polio and other enteroviruses in four wastewater treatment plants in three cities in Italy, using different treatment systems. Detection of enteroviruses was carried out by virus isolation in cell cultures after concentration of water samples collected at both inlet and outlet of the treatment plants, following the methods described in the WHO guidelines. Viral serotypes isolated before and after water treatment were compared. Forty-eight non-polio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…In contrast, only a few recent investigations have been performed using detailed serotyping of enterovirus strains in Italian wastewaters (32,33,34,52) compared to a higher number of similar studies reported from other countries (53,54,55,56,57,58).…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, only a few recent investigations have been performed using detailed serotyping of enterovirus strains in Italian wastewaters (32,33,34,52) compared to a higher number of similar studies reported from other countries (53,54,55,56,57,58).…”
Section: Discussionmentioning
confidence: 92%
“…Since an infected person excretes 10 7 to 10 13 virus particles per day (19), analysis of incoming sewage may be a useful tool to reveal the presence of and quantify excreted fecal human pathogens and thereby give an estimation of the number of infected persons. Most studies on enteric viruses in sewage only detect the viruses and do not relate the virus sequences identified in sewage to those from patients from the same sampling time and region (27,(35)(36)(37)(38)(39)(40)(41)(42). Several of the techniques for virus detection in sewage have also been developed for detection of poliovirus in line with the WHO polio eradication program (36,(43)(44)(45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of the virus safety of water, enterovirus is often used as a representative, because the discharge of the virus is large and detoxification often needs a long time. The incomplete removal of enterovirus by the wastewater treatment also highlights the resistance and potential health risk for the public after discharging into the natural environment (Battistone et al, 2014).…”
Section: Enterovirusmentioning
confidence: 99%